Mismatch of Talent: Evidence on Match Quality, Entry Wages, and Job Mobility - Fredriksson, Peter; Hensvik, Lena; Skans, Oskar Nordström (American Economic Review, 2018)
We examine the impact of mismatch on entry wages, separations, and wage growth using unique data on worker talents. We show that workers are sorted on comparative advantage across jobs within occupations. The starting wages of inexperienced workers are unrelated to mismatch. For experienced workers, on the other hand, mismatch is negatively priced into their starting wages. Separations and wage growth are more strongly related to mismatch among inexperienced workers than among experienced workers. These findings are consistent with models of information updating, where less information is available about the quality of matches involving inexperienced workers. (JEL D83, J24, J31, J41, J63, J64)